Qualitative and Quantitative Detection of Borax in Food Using Butterfly Pea Flower Extract - Detty Fitriani; Bhakti Karyadi; Euis Nursa'adah (Al Jahiz, 2025)
The detection of borax in food is of critical importance due to its toxic properties, which pose serious health risks, especially when consumed continuously, even in small amounts. Therefore, an environmentally friendly, accessible, and easy-to-use detection method is needed for broader application, particularly in routine food monitoring. This study introduces a novel quantitative detection approach using butterfly pea flower (Clitoria ternatea L.) extract as a natural indicator, combining visual colorimetry and UV-Vis spectrophotometry for dual-mode borax analysis. Unlike previous studies that focused solely on qualitative color observation, this research establishes a quantitative correlation between absorbance and borax concentration, supported by strong linearity (R² = 0.9942) and high sensitivity (LoD = 0.026 ppm; LoQ = 0.088 ppm). The butterfly pea extract, rich in anthocyanins, produced a distinct blue color that shifted to green upon interaction with borax, forming a specific butterfly pea–borax complex with a maximum wavelength (λmax) at 624 nm. Application to real meatball samples revealed borax contents of 0.528% and 0.4641% in two samples, respectively. The integration of butterfly pea extract with turmeric paper as a dual-confirmation system enhances analytical reliability while maintaining cost-effectiveness and environmental safety. This work contributes a validated, eco-friendly, and quantitative natural detection method that bridges the gap between laboratory precision and community-based food safety monitoring.